A Rare Case of Small Bowel Obstruction in a Patient with Endosalpingiosis, Fitz-Hugh-Curtis Syndrome, and Chlamydia trachomatis Pelvic Inflammatory Disease - Zhi Kiat Sia; Jodie Trautman; Takako Eva Yabe; James Wykes (Case Reports in Surgery)
A 19-year-old female has multiple presentations to emergency department with recurrent abdominal pain. During her third presentation, the radiological features were suggestive of high-grade small bowel obstruction in a virgin abdomen. A diagnostic laparoscopy has been performed. The intraoperative findings include a band adhesion between omentum and small bowel mesentery, and perihepatic adhesions consistent with Fitz-Hugh-Curtis syndrome. The histopathology from a biopsy of the macular lesions of the abdominal wall showed endosalpingiosis. The postoperative high vaginal swab was positive for Chlamydia trachomatis. The underlying cause of her small bowel obstruction could be due to pelvic inflammatory disease, Fitz-Hugh-Curtis syndrome, or endosalpingiosis. We aimed to create awareness amongst readers that small bowel obstruction in young female patients with no prior abdominal surgery is possible and often difficult to diagnose immediately.